Marburg variant of multiple sclerosis: A young women case report - Mohammed Alaa Jameel; Wameth Alaa Jamel; Alaa Jameel Hasan; Riyam Amer Hammood Alkhuzaie (Radiology Case Reports)
Marburg disease (malignant multiple sclerosis, MS) is a rare, acute MS variant, predominantly occurring among young adults. Because it is characterized by rarity, high morbidity and mortality rates, the disease needs to be further characterized, and the experience of the physicians play a role in treatment regimens. We report the case of a 15-years-old female presenting with progressive weakness over the limbs, hyperreflexia and loss of sensation by physical examination, lab tests and radiological investigations (MRI). After treatment, nonimprovement was recognized by symptoms review after IV corticosteroids, Gabapentin and Clonazepam intake during a clinical visit. IV corticosteroids, Gabapentin and Clonazepam are not sufficient treatment for Marburg's variant of multiple sclerosis disease. Therefore, aggressive therapies can be used to further suppress the inflammatory process to prevent further neurological damage.